Validating Prison Security Classification Instruments in Hawaii, 1984-1985 - Downs, George W. ([Verlag nicht ermittelbar], 1993)
The purpose of this study was to develop and validate a reliable and accurate method for measuring the effectiveness of offender classification systems to improve the management of correctional facilities. In the early 1980s, the state of Hawaii began classifying its prisoners with a newly developed Federal Bureau of Prisons classification instrument. This study was designed to develop a method to evaluate this form. Two prediction models were used. The first, initial classification, used the sum of four variables to arrive at a security score, which was taken to be predictive of violence. The second, reclassification, used the sum of seven different variables to obtain a custody total, which was then used as a major determinant of reclassification. Two groups of inmates were used: inmates who had committed infractions and inmates with no reported infractions. Research variables include (a) initial classification: offense (severity), expected length of incarceration (sentence), type of prior commitments, and history of violence, and (b) reclassification: percentage of time served, involvement with drugs/alcohol, mental/psychological stability, most serious disciplinary report, frequency of disciplinary reports, responsibility that the inmate demonstrated, and family/community ties. In addition, the collection supplies information on race and sex of inmates, sentence limitation, history of escapes or attempts, previous infractions, entry, reclassification, and termination dates (month and year), and custody level. There are demographic variables for sex and race. The unit of observation is the inmate.